Calculation of Tsunami Wave Run-Up and Velocity in Sidangoli Bay, West Halmahera - Rohima Wahyu Ningrum Ningrum; Indriati Retno Palupi Palupi; Rahim Achmad; Suryani Taib; Ramdani Salam Salam; Saprudin Saprudin (Wahana : Tridarma Perguruan Tinggi, 2025)
Due to its complex and unique geological tectonic system, North Maluku is prone to tsunami hazards. The cause of the tsunami is likely to be a megathrust earthquake. Although there are few casualties and only localized tsunamis, they significantly affect the region's stability. One of the areas recorded by the Indonesian paleo tsunami database on 28 June 1859, when a strong earthquake occurred in the Maluku Sea with a magnitude of 7, was Sidangoli Bay, with a tsunami wave run-up of 10 meters. Therefore, it is necessary to calculate the run-up and velocity of tsunami waves to mitigate tsunami disasters. The calculation method uses mathematical equations with a Python program combining various parameters. The data processing resulted in tsunami modelling showing the run-up value and tsunami wave speed in Sidangoli Bay, South Jailolo. The tsunami wave propagation speed reached 80 meters/second, and the tsunami wave height reached 28 meters. The run-up and velocity of tsunami waves in Sidangoli Bay are significant and may destroy anything in their path.